Local sea level rise scenarios for the end of the 21st century and potential physical impacts in the lower Ria de Aveiro (Portugal) - Lopes, C. L. (2011)
Sea level change is an important consequence of climate change due to its impact on society and ecosystems. Analyses of tide-gauge data have indicated that the global sea level has risen during the 20th century and several studies predict that the mean sea level will continue to rise during the 21st century, intensifying coastal hazards worldwide. In Portugal, the Ria de Aveiro is expected to be one of the regions most affected by sea level change. The main aim of this study is to evaluate the potential impacts of the mean sea level change on the hydrodynamics and morphodynamics of the Ria de Aveiro. With this purpose, local mean sea level change was projected for the period 2091–2100 relative to 1980–1999, for different Special Report on Emission Scenarios (SRES) scenarios developed by the Intergovernmental Panel on Climate Change (IPCC). These projections revealed an increase in the mean sea level between 0.28 m under scenario B1 and 0.42 m under scenario A2. The results obtained for sea level rise scenario A2 projection were used to force the morphodynamic model MORSYS2D, previously implemented for the Ria de Aveiro. The modelling results were compared with model forecasts for the present sea level. The residual sediment transport and its balance at the lagoon inlet were computed and analysed for both situations. While the residual sediment transport is generally seaward, sediments tend to deposit inside the inlet due to the weak sediment transport at its mouth. The direction of the residual flux will not change with the sea level rise, but sediment fluxes will intensify, and accretion inside the inlet will increase. The rise in mean sea level will also affect the lagoon hydrodynamics. The tidal prism at the lagoon mouth will increase by about 28% in spring tide. In the lower lagoon only a slight increase of the tidal asymmetry is predicted.